Factors influencing event media personnel's frame building process at the 2018 FIFA World Cup Russia. (October 2022) - Sobral, Vitor; Fairley, Sheranne; O'Brien, Danny
Abstract: Holding major events has the capacity to improve a host city's tourism image. Effective event leverage for image benefits requires host destinations to implement strategies to influence event media coverage in the lead up, during, and after the event. This research takes a media frame building perspective to understand the processes behind how event media personnel frame coverage of an event host. Fourteen semi-structured interviews were conducted with event media personnel at the 2018 FIFA World Cup Russia. We developed a grounded theory model that depicts how event media personnel's pre-event frame repository and event period experiences influenced their perceptions and potential frames of the host destination. We advance knowledge of event leveraging, and media framing theory, by demonstrating the importance of experience and unofficial sources in event media framing. This knowledge can be used by stakeholders involved in event leveraging to better design strategies aimed at positively influencing media coverage of events.